Modified positive electrode material and preparation method and application thereof

By forming a mesh-chain-shaped cladding layer of two-dimensional MOF material on the surface of the layered positive electrode material, the stability of the layered positive electrode material in lithium-ion batteries is solved, and the high-temperature cycle and large-scale charge and discharge stability is significantly improved, and the charging and discharge stability is extended. Battery life and improve electrochemical performance.

CN119153657APending Publication Date: 2024-12-17ZHEJIANG LIWINON ENERGY TECHNOLOGY CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411331419.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-24
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

The existing layered positive electrode materials have problems such as poor long-term cycle stability, poor high-temperature cycle stability, and poor large-scale charge and discharge stability in lithium-ion batteries, which affect the safety performance and service life of lithium-ion batteries.

Method used

A two-dimensional MOF material is used as the cladding layer, and a mesh-shaped cladding layer is formed by in-situ deposition on the surface of the layered positive electrode material to enhance structural stability and suppress side reactions in the electrolyte interface, improving the stability in cycle and magnification tests.

Benefits of technology

It significantly improves the high-temperature cycle stability and large-scale charge and discharge stability of the modified positive electrode material, extends the service life of lithium-ion batteries and improves the electrochemical performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119153657A_ABST
    Figure CN119153657A_ABST
Patent Text Reader

Abstract

The invention discloses a modified positive electrode material and a preparation method and application thereof, and belongs to the technical field of secondary battery raw materials. The modified positive electrode material provided by the invention comprises a layered positive electrode material; the chemical formula of the layered positive electrode material is LiXO2, wherein X is at least one of Ni, Co and Mn; the coating layer is a two-dimensional MOF material which is deposited on the surface of the layered positive electrode material in situ; the molar ratio of X in the layered positive electrode material to a central atom in the two-dimensional MOF material is 1: (0.1-2.0). According to the modified positive electrode material provided by the invention, the high-temperature cycling stability and the high-rate charge-discharge stability of the modified positive electrode material can be effectively improved. The invention also provides a preparation method and application of the modified positive electrode material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of secondary battery raw materials, and in particular to a modified positive electrode material and a preparation method and application thereof. Background Art

[0002] In lithium-ion batteries, the positive electrode material is usually a layered positive electrode material with the general chemical formula LiXO2 (X is one of Ni, Co, and Mn); during the charge and discharge process, due to the continuous deintercalation and intercalation of lithium, the Jaha-Teller effect is prone to occur, which leads to structural changes in the layered positive electrode material, and even changes in the crystal form, and the electrochemical performance is reduced; the interfacial side reactions between the layered positive electrode material and the electrolyte will also cause electrolyte decomposition and gas production; at the same time, there are also problems such as the dissolution of the metal element X. The above problems lead to the shortcomings of LiXO2, such as poor long-term cycle stability, poor high-temperature cycle stability, and poor high-rate charge and discharge stability, which in turn affect the safety performance of lithium-ion batteries and damage the service life of lithium-ion batteries.

[0003] In order to solve the above problems, the related art attempts to coat and / or dope the layered positive electrode material in order to stabilize its lattice structure or isolate the contact between the layered positive electrode material and the electrolyte.

[0004] However, the doping technology is difficult to operate and consumes a lot of energy, and the coating has limited effect on improving performance. Therefore, the existing layered positive electrode materials still have problems such as poor long-term cycle stability, poor high-temperature cycle stability, and poor high-rate charge and discharge stability. Summary of the invention

[0005] The present invention aims to solve at least one of the technical problems existing in the prior art. To this end, the present invention provides a modified positive electrode material that can effectively improve its high temperature cycle stability and high rate charge and discharge stability.

[0006] The present invention also provides a method for preparing the modified positive electrode material.

[0007] The present invention also provides application of the modified positive electrode material.

[0008] According to an embodiment of the first aspect of the present invention, a modified positive electrode material is provided, wherein the modified positive electrode material comprises:

[0009] Layered positive electrode material; the chemical formula of the layered positive electrode material is LiXO2, wherein X is at least one of Ni, Co and Mn;

[0010] A coating layer, wherein the coating layer is a two-dimensional MOF material deposited in situ on the surface of the layered positive electrode material;

[0011] The molar ratio of the transition metal atom X in the layered positive electrode material to the central atom in the two-dimensional MOF material is 1:(0.1-2.0).

[0012] The modified positive electrode material according to the embodiment of the present invention has at least the following beneficial effects:

[0013] Compared with three-dimensional MOF materials, the present invention adopts two-dimensional MOF materials as coating layers, thereby, the two-dimensional MOF materials can form a network chain coating on the surface of the layered positive electrode material, that is, form a protective net, which has strong stress and deformation resistance stability, and can enhance its structural stability when the layered positive electrode material undergoes volume change and phase change during charging and discharging, and can also broaden the charge and discharge boundary limits of the obtained modified positive electrode material; thereby, its stability in cycle and rate tests can be improved to a certain extent.

[0014] According to some embodiments of the present invention, the ligand of the two-dimensional MOF material is terephthalic acid. The ligand has a benzene ring structure with strong structural stability, and the structure does not change during the formation of the two-dimensional MOF material; combined with the two-dimensional structure of the coating layer, the benzene ring structure can be evenly distributed on the surface of the layered positive electrode material, which is equivalent to wrapping the layered positive electrode material with a layer of organic film with a benzene ring structure, which can play a good inhibitory effect on the side reaction of the interface between the layered positive electrode material and the electrolyte. The various stabilities of the obtained modified positive electrode material are further improved.

[0015] Within the scope provided by the present invention, as the thickness of the coating layer increases, the electrochemical performance of the modified cathode material shows a trend of first rising and then falling, reaching a peak at about 1:1.5. The reason is that a small number of layers of two-dimensional MOF material (when the coating layer is thin) can alleviate the side reactions between the layered cathode material and the electrolyte and enhance the electronic and ionic conductivity, but once the coating layer is too thick, the contact between the layered cathode material and the electrolyte becomes less, that is, the wettability of the modified cathode material becomes worse, which will affect the electrochemical performance to a certain extent; in addition, if the amount of two-dimensional MOF material is too small, a complete coating layer cannot be formed, and the incompletely coated two-dimensional MOF material will increase the occurrence of side reactions.

[0016] According to some embodiments of the present invention, the layered positive electrode material includes at least one of lithium cobalt oxide, lithium manganese oxide, lithium nickel oxide and lithium nickel cobalt manganese oxide.

[0017] According to some embodiments of the present invention, the molar ratio of the transition metal atom X in the layered cathode material to the central atom in the two-dimensional MOF material is 1:(0.1-1.5), for example, about 1:0.3, 1:0.5, 1:0.8, 1:1.0 or about 1:1.2.

[0018] According to some embodiments of the present invention, the central atom of the two-dimensional MOF material is at least one of Ni, Co, Mn, Al, Fe, Mg, Cu, Zn, Ti and Zr. The central atom has a special electron cloud orbit, and there is a certain synergistic effect between it and the transition metal atom (X) in the layered positive electrode material, which has an enhancing effect on the stability of X, and specifically can effectively alleviate the dissolution problem of X. In addition, the two-dimensional MOF material having the above central atom and ligand can significantly improve the electronic conductivity and ionic conductivity of the obtained modified positive electrode material.

[0019] According to some embodiments of the present invention, the central atom of the two-dimensional MOF material is Zr.

[0020] According to some embodiments of the present invention, the central atom of the two-dimensional MOF material is Mg.

[0021] According to some embodiments of the present invention, the central atoms of the two-dimensional MOF material are two of Ni, Co, Mn, Al, Fe, Mg, Cu, Zn, Ti and Zr.

[0022] According to some embodiments of the present invention, the central atom of the two-dimensional MOF material is a combination of Zr and Co, a combination of Mg and Co, or a combination of Ni and Co.

[0023] According to some embodiments of the present invention, the molar ratio of the two central atoms is 1:(0.1-9), for example, about 1:0.2, 1:0.3, 1:0.5, 1:0.6, 1:0.8, 1:1, 1:1.2, 1:1.5, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7 or about 1:8.

[0024] According to some embodiments of the present invention, the molar ratio of the two central atoms is (1-4):(1-4).

[0025] According to an embodiment of the second aspect of the present invention, there is provided a method for preparing the modified positive electrode material, the method comprising the following steps:

[0026] S1. mixing the layered cathode material, the ligand of the two-dimensional MOF material, and the central atomic source in water;

[0027] S2. subjecting the mixture obtained in step S1 to a hydrothermal reaction.

[0028] The mechanism of the preparation method is as follows:

[0029] In step S2, the central atom in the central atom source and the ligand self-assemble on the surface of the layered positive electrode material to form a coating layer having a two-dimensional network chain shape.

[0030] Since the preparation method adopts all the technical solutions of the modified positive electrode material of the above embodiment, it at least has all the beneficial effects brought by the technical solutions of the above embodiment.

[0031] The present invention can adjust the stacking direction of the obtained MOF material by limiting the specific solvent, that is, the obtained MOF material is a two-dimensional MOF material instead of a three-dimensional MOF material.

[0032] The preparation method provided by the present invention is simple to operate and mature, and is convenient for large-scale promotion and use of the modified positive electrode material.

[0033] According to some embodiments of the present invention, in step S1, the layered cathode material is purchased from a commercial source or prepared in-house, wherein the preparation in-house comprises mixing a lithium source and a precursor and then calcining the mixture.

[0034] The lithium source includes at least one of lithium hydroxide and lithium carbonate.

[0035] The precursor includes an oxide of X or a hydroxide of X.

[0036] The precursor includes cobalt tetroxide.

[0037] The mass ratio of the lithium source to the precursor is 1:(2-2.1).

[0038] The calcination includes a first stage calcination and a second stage calcination which are performed sequentially.

[0039] The temperature of the first stage calcination is 500-600°C; for example, it can be about 550°C.

[0040] The duration of the first calcination stage is 0.5 to 1.5 hours; for example, it may be about 1 hour.

[0041] The temperature of the second stage calcination is 800-1000°C; for example, it can be about 850°C, 900°C or about 950°C.

[0042] The duration of the second calcination stage is 8 to 10 hours; for example, it may be about 8.5 hours, 9 hours or about 9.5 hours.

[0043] According to some embodiments of the present invention, in S1, the mass volume ratio of the layered positive electrode material to water is 2 to 3.5 g / mL, for example, about 2.5 g / mL or about 3 g / mL.

[0044] According to some embodiments of the present invention, in step S1, the mixing further comprises adding hydrofluoric acid, so that the mixture obtained in step S1 is weakly acidic, thereby preventing the hydrolysis of the central atomic source.

[0045] According to some embodiments of the present invention, the volume ratio of the hydrofluoric acid to the water used in step S1 is 1:(40-50), for example, about 1:45 or about 1:47.

[0046] According to some embodiments of the present invention, in step S1, the molar ratio of the ligand to the central atom source is 1:(0.8-1.2); for example, it may be about 1:1.

[0047] According to some embodiments of the present invention, in step S1, the central atomic source includes at least one of ZrCl4·8H2O, MgCl2·6H2O, CoCl2·6H2O and NiCl2·6H2O.

[0048] According to some embodiments of the present invention, in step S1, the mixing comprises the following steps:

[0049] S1a. Mix water and hydrofluoric acid;

[0050] S1b. The mixture obtained in step S1a is mixed with the ligand;

[0051] S1c. The mixture obtained in step S1b is mixed with the central atomic source;

[0052] S1d. Mixing the mixture obtained in step S1c and the layered positive electrode material.

[0053] According to some embodiments of the present invention, in step S1b, the mixing time is 10 to 20 minutes; for example, it can be about 150 minutes. More specifically, the mixing includes stirring and ultrasound in sequence. More specifically, the stirring time is about 5 minutes; the ultrasound time is about 10 minutes. In this way, the ligand can be fully dissolved.

[0054] According to some embodiments of the present invention, in step S2, the temperature of the hydrothermal reaction is 150-300°C, for example, about 160°C, 180°C, 200°C, 220°C, 240°C, 260°C or about 280°C.

[0055] Within this temperature range, the electrochemical performance of the modified cathode material showed a trend of first increasing and then decreasing, reaching a peak at about 240°C.

[0056] According to some embodiments of the present invention, in step S2, the duration of the hydrothermal reaction is 10 to 36 hours, for example, about 12 hours, 14 hours, 16 hours, 18 hours, 20 hours, 22 hours, 24 hours, 26 hours, 28 hours, 30 hours, 32 hours or about 34 hours.

[0057] According to some embodiments of the present invention, the preparation method further comprises step S3 performed after step S2:

[0058] S3. The mixture obtained in the solid-liquid separation step S2 is dried and crushed to obtain a solid product.

[0059] According to some embodiments of the present invention, in step S3, the drying temperature is 110-150°C, for example, about 120°C, 130°C or about 140°C.

[0060] According to some embodiments of the present invention, in step S3, the drying time is 4 to 8 hours, for example, about 5 hours, 6 hours or about 7 hours.

[0061] According to some embodiments of the present invention, in step S3, the drying method includes vacuum drying.

[0062] According to some embodiments of the present invention, in step S3, the crushing method includes grinding.

[0063] According to an embodiment of the third aspect of the present invention, a lithium-ion battery is provided, wherein raw materials for preparing the lithium-ion battery include the modified positive electrode material.

[0064] Since the lithium-ion battery adopts all the technical solutions of the modified positive electrode material of the above embodiment, it has at least all the beneficial effects brought by the technical solutions of the above embodiment.

[0065] According to some embodiments of the present invention, the lithium-ion battery includes a positive electrode, a negative electrode, a separator disposed between the positive electrode and the negative electrode, and an electrolyte that soaks the above components; wherein,

[0066] The positive electrode comprises a positive electrode current collector and a positive electrode coating disposed on the surface of the positive electrode current collector;

[0067] The raw material for preparing the positive electrode coating includes the modified positive electrode material.

[0068] According to some embodiments of the present invention, the raw materials for preparing the positive electrode coating further include a positive electrode conductor and a positive electrode binder.

[0069] The positive electrode conductive agent includes acetylene black.

[0070] In the positive electrode coating, the mass percentage of the positive electrode conductive agent is 1-5%, for example, specifically about 2% or about 3%.

[0071] The positive electrode binder includes PVDF.

[0072] In the positive electrode coating, the mass percentage of the positive electrode binder is 1-5%, for example, specifically about 2% or about 3%.

[0073] In the positive electrode coating, the mass percentage of the modified positive electrode material is 90-98%, for example, specifically about 92%, 94% or about 96%.

[0074] According to some embodiments of the present invention, the negative electrode includes a negative electrode current collector and a negative electrode coating disposed on a surface of the negative electrode current collector.

[0075] The raw materials for preparing the negative electrode coating include negative electrode active material, negative electrode conductive agent, negative electrode binder and thickener.

[0076] The negative electrode active material includes at least one of graphite and a silicon-based material.

[0077] In the negative electrode coating, the mass percentage of the negative electrode active material is 90-98%, for example, specifically about 92%, 94% or about 96%.

[0078] The negative electrode conductive agent includes at least one of carbon nanotubes and acetylene black.

[0079] In the negative electrode coating, the mass percentage of the negative electrode conductive agent is 0.5-1.5%, for example, specifically about 1%.

[0080] The negative electrode binder includes styrene-butadiene rubber.

[0081] In the negative electrode coating, the mass percentage of the negative electrode binder is 0.2-1%, for example, it may be about 0.4%, 0.6% or about 0.8%.

[0082] The thickener includes sodium carboxymethylcellulose.

[0083] In the negative electrode coating, the mass percentage of the thickener is 0.2-1%, for example, it can be about 0.4%, 0.6% or about 0.8%.

[0084] According to some embodiments of the present invention, the material of the diaphragm includes polyethylene.

[0085] According to some embodiments of the present invention, the electrolyte includes a lithium salt and an organic solvent.

[0086] The lithium salt includes lithium hexafluorophosphate;

[0087] In the electrolyte, the mass percentage of lithium salt is 5-15%, for example, about 7%, 9%, 10%, 11% or about 13%.

[0088] The organic solvent includes at least one of a carboxylate and a carbonate.

[0089] The organic solvent is a mixture of ethylene carbonate (EC), propyl propionate (PP), vinylene carbonate (VC), diethyl carbonate (DEC) and propylene carbonate (PC) in a mass ratio of 25:(18-22):(3-5):(25-30):(20-25).

[0090] According to an embodiment of the fourth aspect of the present invention, there is provided an application of the lithium-ion battery in the fields of energy storage, power and 3C consumer electronic products.

[0091] Since the application adopts all the technical solutions of the modified positive electrode material of the above embodiment, it has at least all the beneficial effects brought by the technical solutions of the above embodiment.

[0092] If there is no special explanation, the actual meaning of “about” in the present invention is that the error is allowed to be within the range of ±2%, for example, about 100 is actually 100±2%×100.

[0093] Unless otherwise specified, “between” in the present invention includes the number itself, for example, “between 2 and 3” includes the endpoint values ​​2 and 3.

[0094] Other features and advantages of the present invention will be set forth in the description which follows, and in part will be apparent from the description, or may be learned by practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0095] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:

[0096] Figure 1 It is a schematic diagram of the structure of the modified positive electrode material obtained in the embodiment of the present invention. DETAILED DESCRIPTION

[0097] The following will be combined with the embodiments to clearly and completely describe the concept of the present invention and the technical effects produced, so as to fully understand the purpose, characteristics and effects of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present invention.

[0098] In the description of the present invention, the description with reference to the terms "one embodiment", "some embodiments", "illustrative embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.

[0099] Material Preparation Example

[0100] In this example, a layered positive electrode material was prepared. The specific steps are as follows:

[0101] 750 g of lithium carbonate and 1526 g of cobalt tetroxide (purchased from Sinopharm Chemical Reagent Co., Ltd.) were added to a blender and stirred at 1500 r / min for 1 h to obtain a mixture. The mixture was annealed at 550° C. for 1 h and then sintered at 900° C. for 9 h to obtain a layered positive electrode material made of lithium cobalt oxide.

[0102] Unless otherwise specified, the layered positive electrode materials used in the specific implementation methods are all from this example.

[0103] The quality of the prepared raw materials is only used to indicate the proportion, and does not represent the actual quality. In actual production, the output can be proportionally increased or decreased according to demand.

[0104] Example 1

[0105] In this example, a modified positive electrode material was prepared, and the specific steps were as follows:

[0106] S1. Prepare the mixed system for hydrothermal reaction:

[0107] S1a. Take 140 mL of deionized water in a 200 mL hydrothermal reactor and add 3 mL of hydrofluoric acid (HF) to adjust the solution to be weakly acidic;

[0108] S1b. Add terephthalic acid (HBDC) to the mixture obtained in step S1a and stir for 5 min, and then perform ultrasound for 10 min to dissolve terephthalic acid (HBDC);

[0109] S1c. Add ZrCl4·8H2O to the mixture obtained in step S1b, wherein the molar ratio of HBDC to Zr is 1:1.

[0110] S1d. Add 48.9 g of lithium cobalt oxide obtained in the material preparation example to the mixture obtained in step S1c, wherein the molar ratio of cobalt in the lithium cobalt oxide to Zr in ZrCl4·8H2O is 1:0.1.

[0111] S2. The mixture obtained in step S1 is transferred to an environment of 210° C. and heated for 24 hours; and then cooled naturally to room temperature. During the process, terephthalic acid and ZrCl4·8H2O self-assemble on the surface of lithium cobalt oxide to form a two-dimensional MOF material.

[0112] S3. The mixture obtained in step S2 is separated into solid and liquid, and the solid product is vacuum dried at a temperature of 130° C. for 6 hours. The solid material obtained after drying is ground to obtain a modified positive electrode material.

[0113] The structural schematic diagram of the modified positive electrode material obtained in this example is as follows Figure 1 As shown, it specifically includes lithium cobalt oxide and a two-dimensional MOF material wrapped on the surface of the lithium cobalt oxide, and the two-dimensional MOF material forms a network structure.

[0114] Examples 2 to 19 and Comparative Examples 3 to 6 respectively prepared a modified positive electrode material, which differed from Example 1 in that:

[0115] In step S1d, the molar ratio of cobalt in lithium cobalt oxide to the central atom of the central atom source;

[0116] And / or, in step S1c, the composition of the central atomic source is different.

[0117] The specific differences are shown in Table 1. Among them, cobalt: central atom refers to the molar ratio of cobalt in lithium cobalt oxide to the central atom in the two-dimensional MOF material.

[0118] Table 1 Comparison of some parameters of Examples 1 to 19 and Comparative Examples 3 to 6

[0119]

[0120]

[0121] Comparative Example 1

[0122] In this example, the lithium cobalt oxide obtained in the material preparation example is directly used as the positive electrode material.

[0123] Comparative Example 2

[0124] In this example, a modified positive electrode material was prepared, and the specific steps were as follows:

[0125] A1. Dissolve ZrCl4 and 1,4-phthalic acid (H2BDC, 0.25 mol) in 200 mL of N,N-dimethylformamide (DMF) at room temperature in a molar ratio of H2BDC:Zr=1:1, stir evenly, and then add lithium cobalt oxide in a molar ratio of lithium cobalt oxide:Zr=1:1.0;

[0126] A2. The mixture obtained in step A1 was transferred to a reaction vessel and heated at 130°C for 24 hours; after heating, the mixture was naturally cooled to room temperature.

[0127] A3. The mixture obtained in step A2 is separated into solid and liquid, and the solid product is vacuum dried at a temperature of 110°C for 6 hours. The solid material obtained after drying is ground to obtain a modified positive electrode material.

[0128] In this example, due to differences in solvent and solvent thermal reaction temperature during the preparation process, ZrCl4 and 1,4-phthalic acid form a three-dimensional MOF material, which is deposited on the surface of lithium cobalt oxide, referred to as UIO-66(Zr).

[0129] Application Examples

[0130] In this example, a lithium-ion battery was prepared. The specific process is as follows:

[0131] Preparation of positive electrode: The positive electrode active material (the product of the embodiment or comparative example), the positive electrode conductive agent acetylene black, and the positive electrode binder polyvinylidene fluoride (PVDF) are fully stirred in an N-methylpyrrolidone solvent system at a mass ratio of 96:3:2. After stirring evenly, a positive electrode slurry is obtained, and the slurry is coated on an Al foil (positive electrode current collector), baked, rolled, and cut into strips to obtain a positive electrode.

[0132] Preparation of negative electrode: Graphite (negative electrode active material), negative electrode conductive agent carbon nanotube, negative electrode binder styrene butadiene rubber, and thickener sodium carboxymethyl cellulose are stirred and mixed in deionized water at a mass ratio of 97.5:1.3:0.6:0.6. After being mixed evenly, the obtained negative electrode slurry is coated on Cu foil (negative electrode current collector), baked, rolled, and cut into strips to obtain the negative electrode.

[0133] Diaphragm: Polyethylene (PE) polymer film.

[0134] Electrolyte: Organic solvents of ethylene carbonate (EC), propyl propionate (PP), vinylene carbonate (VC), diethyl carbonate (DEC) and propylene carbonate (PC) were mixed in a mass ratio of 25:20:4:27:24. Lithium salt LiPF6 was added to the obtained mixed organic solution, and the mass percentage of the added lithium salt was 9.5%.

[0135] Assembly: Stack the positive electrode, separator, and negative electrode in order, and wind them to obtain an electrode assembly. When folding the electrode sheets, pay attention to the separator to completely separate the positive and negative electrode sheets. Put the electrode assembly in the packaging shell, inject the electrolyte into the packaging shell and package it, and finally obtain a lithium-ion battery.

[0136] Test Case

[0137] This example tests the electrochemical performance of the lithium-ion battery obtained in the application example. The specific test items and methods are as follows:

[0138] (1) Gram capacity test:

[0139] Six samples were taken from each group of lithium-ion batteries and charged to 4.55V at room temperature under constant current and constant voltage conditions at a rate of 0.5C, with a cut-off current of 0.02C. Then, constant current discharge was performed at a rate of 0.5C until the voltage was cut off at 3.0V. The obtained capacity was recorded, and the obtained capacity was divided by the mass of the positive electrode active material to obtain the gram capacity of the product obtained in the embodiment or comparative example. In the gram capacity test and other tests, 1C was set to 167mA / g.

[0140] (2) Cyclic performance test:

[0141] Six samples were taken from each group of lithium-ion batteries, and their cycle performance was tested at 45°C. The detailed steps were as follows: charge to 4.55V at 3C constant current and constant voltage, with a cut-off current of 0.02C, and discharge to 3.0V at 1.0C constant current. This first charge and discharge process is one cycle. Repeat this cycle step until the capacity retention rate of the lithium-ion battery is less than 80%. The cycle test is over, and the cycle number of the lithium-ion battery is recorded.

[0142] (3) Rate performance test:

[0143] Take 6 samples from each group of lithium-ion batteries, charge to 4.55V under constant current and constant voltage conditions at a rate of 0.2C, and the cut-off current is 0.02C. Then, discharge at a constant current at a rate of 0.2C until the voltage is cut off at 3.0V. The discharge capacity at this step is A1. Charge to 4.55V under constant current and constant voltage conditions at a rate of 0.2C, and the cut-off current is 0.02C. Then, discharge at a constant current at a rate of 2.5C until the voltage is cut off at 3.0V. The discharge capacity at this step is A2. The discharge capacity percentage obtained by A2 / A1*100% is the rate performance test result.

[0144] The statistical results of the above tests are shown in Table 2.

[0145] Table 2 Electrochemical performance results of the modified positive electrode materials obtained in the examples and the positive electrode materials obtained in the comparative examples

[0146]

[0147]

[0148] From the results of Table 1, it can be seen that the two-dimensional MOF material is used to in-situ assemble and coat the lithium cobalt oxide matrix material. As the coating layer forms a network chain coating on the surface of the lithium cobalt oxide, the electrochemical properties of the modified positive electrode material such as gram capacity, high temperature cycle and rate discharge are greatly improved. This is mainly because the two-dimensional MOF material coated with a network chain has strong stress and deformation stability. The crystal phase change of lithium cobalt oxide during charging and discharging is suppressed, the structural stability of the modified positive electrode material is enhanced, the limit of its charge and discharge boundary is broadened, and then its electrochemical properties, especially the cycle stability, are enhanced. In addition, in the coating layer used in the present invention, the organic ligand terephthalic acid contains a benzene ring structure, which has a strong structural stability, and the structure does not change in the network chain coating, which is equivalent to surrounding a layer of benzene ring structure organic film on the surface of the lithium cobalt oxide. In the contact between the modified positive electrode material and the electrolyte, the interfacial side reaction between the modified positive electrode material and the electrolyte can be effectively suppressed, which has a strengthening effect on the cycle stability of the modified positive electrode material. Further specific:

[0149] The results of the examples and comparative examples 1 to 2 show that if the surface of lithium cobalt oxide is not coated, or coated with a three-dimensional MOF material (Comparative Examples 1 to 2), its overall electrochemical performance is poor. This is because the three-dimensional MOF material cannot form a network structure and does not have anti-deformation stability, so it does not have the effect of improving its structural stability. Furthermore, the three-dimensional MOF material and the two-dimensional MOF material have different forms of transmitting electrons and ions, and the effect of improving the electronic conductivity and ionic conductivity of the obtained modified positive electrode material is not obvious.

[0150] The results of Examples 1 to 10 and Comparative Examples 3 to 6 show that when the two-dimensional MOF material is a material with a single central atom such as Zr-MOF or Mg-MOF, the molar ratio between the cobalt in the lithium cobaltate and the central atom in the two-dimensional MOF material is in the range of 1: (0.1 to 1). As the coating layer increases, the electrochemical performance of the resulting modified positive electrode material is improved. Once this range is exceeded, the electrochemical performance shows a downward trend. If the dosage ratio of the central atom is less than 1: 0.1, or exceeds 1: 2.0, the performance deteriorates significantly, even lower than the lithium cobaltate material without any modification in Comparative Example 1. This is because the appropriate amount of mesh chain coating layer located on the surface of the lithium cobaltate can effectively enhance its structural stability, reduce the occurrence of side reactions between the lithium cobaltate and the electrolyte, and enhance ion and electron conduction. However, once the amount of the coating layer is excessive, it is easy to cause multi-layer assembly coating (the two-dimensional MOF material has a multi-layer structure), reduce ion and electron conductivity, and cause electrochemical performance to decrease. If the coating amount is insufficient, a complete coating layer cannot be formed, and the coating material instead acts as an impurity, thereby reducing the overall performance of the obtained modified positive electrode material.

[0151] The results of Examples 11 to 17 show that when the two-dimensional MOF material is a dual-central atom MOF material, when the molar ratio of the two central atoms is 1:1, the electrochemical performance of the resulting modified positive electrode material is optimal. This is because, near this ratio, the two central atoms are most evenly distributed on the surface of lithium cobalt oxide and their synergistic effect is optimal.

[0152] The central atom Zr of the two-dimensional MOF material can enhance the ion diffusion rate of the modified cathode material, increase its discharge rate, and improve its phase change reversibility; Co can provide electrons during the charge and discharge process of the modified cathode material, increase the number of electrons in its charge and discharge upper limit, increase the electron transfer rate, and increase the gram capacity. That is, compared with other types of two-dimensional MOF materials, in Zr / Co-MOF, there will be a certain synergistic effect between the two central atoms, which significantly improves the gram capacity, high temperature cycle stability, and rate performance of the obtained modified cathode material.

[0153] By comparing Examples 8, 14 and 18 to 19, it can be seen that if the two-dimensional MOF material is Mg / Co-MOF, the central atom and lithium cobalt oxide can still play a synergistic role, but the synergistic effect is inferior to the synergistic effect of Zr and Co. Similarly, if the two-dimensional MOF material is Ni / Co-MOF, the obtained modified cathode material can still achieve relatively excellent electrochemical performance.

[0154] In summary, the modified cathode material provided by the present invention forms a coating layer of a two-dimensional MOF material on its surface, and the special structure, special material, specific dosage of the coating layer and the layered cathode material have a synergistic effect, which significantly improves the capacity, cycle stability and rate performance of the obtained modified cathode material. It is precisely because of the above excellent performance that lithium-ion batteries including the above modified cathode materials are expected to be widely used in the power field (such as electric vehicles), energy storage field and 3C consumer electronic products.

[0155] The embodiments of the present invention are described in detail above in conjunction with the accompanying drawings, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge of ordinary technicians in the relevant technical field without departing from the purpose of the present invention. In addition, the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.

Claims

1. A modified positive electrode material, characterized in that: The modified positive electrode material comprises: Layered positive electrode material; the chemical formula of the layered positive electrode material is LiXO2, wherein X is at least one of Ni, Co and Mn; A coating layer, wherein the coating layer is a two-dimensional MOF material deposited in situ on the surface of the layered positive electrode material; The molar ratio of X in the layered positive electrode material to the central atom in the two-dimensional MOF material is 1:(0.1-2).

2. The modified positive electrode material according to claim 1, characterized in that The central atom of the two-dimensional MOF material is at least one of Ni, Co, Mn, Al, Fe, Mg, Cu, Zn, Ti and Zr; and / or the ligand of the two-dimensional MOF material is terephthalic acid.

3. The modified positive electrode material according to claim 1, characterized in that The molar ratio of X in the layered positive electrode material to the central atom in the two-dimensional MOF material is 1:(0.1-1.5).

4. The modified positive electrode material according to claim 1, characterized in that The central atoms of the two-dimensional MOF material are two of Ni, Co, Mn, Al, Fe, Mg, Cu, Zn, Ti and Zr; preferably, the molar ratio of the two central atoms is 1:(0.1-9); preferably, the molar ratio of the two central atoms is (1-4):(1-4).

5. The modified positive electrode material according to any one of claims 1 to 4, characterized in that: The central atom of the two-dimensional MOF material is a combination of Zr and Co, a combination of Mg and Co, or a combination of Ni and Co.

6. A method for preparing a modified positive electrode material according to any one of claims 1 to 5, characterized in that: The preparation method comprises the following steps: S1. mixing the layered cathode material, the ligand of the two-dimensional MOF material, and the central atomic source in water; S2. subjecting the mixture obtained in step S1 to a hydrothermal reaction.

7. The preparation method according to claim 6, characterized in that: In step S1, the mixing further comprises adding hydrofluoric acid; and / or the volume ratio of the hydrofluoric acid to the water used in step S1 is 1:(40-50).

8. The preparation method according to claim 6, characterized in that: In step S2, the temperature of the hydrothermal reaction is 150-300°C; and / or, in step S2, the duration of the hydrothermal reaction is 10-36h.

9. A lithium ion battery, characterized in that: The raw materials for preparing the lithium-ion battery include the modified positive electrode material according to any one of claims 1 to 5.

10. Application of the lithium-ion battery according to claim 9 in the fields of energy storage, power and 3C consumer electronic products.

Citation Information

Cited By

  • Battery monomer and preparation method thereof, battery device, power utilization device and energy storage device

    CN121688145A

  • Battery cell, method for producing the same, battery device, electric device, and energy storage device

    CN121688145B